Maternal and Perinatal Outcome in Pregnancies with Oligohydramnios in Third Trimester - Manisha Sharma; D K Bhagwani; Mala Chaurasia; P K Jain (Indian Journal of Neonatal Medicine and Research, 2016)
Introduction: Oligohydramnios presents a threat to the fetus due to increased risk of the umbilical cord getting compressed and resulting in impaired blood flow to the fetus. Aim: The objective of the study was to find out the significance of oligohydramnios during third trimester of pregnancy. Materials and Methods: A hospital based prospective study was conducted in the Department of Obstetrics and Gynaecology at Hindu Rao Hospital, Delhi. Amniotic fluid index (AFI) estimation was done on 150 pregnant women in third trimester, who were selected after screening for inclusion and exclusion criteria. Women with AFI < 5 cm were taken as cases while women with AFI > 5 cm as controls. Results: The mean maternal age was 23.58±3.43 years and maximum women were primigravida. Mean AFI among the cases was 2.97±1.95 cm. Antenatal complications like pre eclampsia, IUGR, PROM were associated with 71% of the cases. Labour was induced in 65% of the cases compared to 21% among controls. LSCS was performed in 44% of cases compared to 10% in controls with fetal distress the most common indication (85%). 73% babies born to the cases had birth weight < 2.5 kg, 55% had APGAR score < 7 and 44% had NICU admission compared to 16%, 13% and 13% respectively among controls. There were 5 intrauterine deaths and 2 stillbirths among the cases and none among the controls. Conclusion: Identification of oligohydramnios can be done by a good clinical examination and confirmed by measuring AFI on ultrasonography. Poor fetal outcome in the form of preterm, IUD, LBW, low APGAR score at 5 minute and increased chances of still birth, NICU admission and neonatal death are seen with oligohydramnios in third trimester and more so if it is detected in early third trimester. Chances of induction of labour and risk of LSCS also increase. Thus, detection of oligohydramnios helps in proper management of the cases so that maternal and perinatal outcome can be improved.